Zemeljski plazovi pri ocenjevanju nevarnosti zaradi delovanja drobirskih tokov - Sodnik, Jošt (Gradbeni vestnik, 2018)
Debris flows present considerable threat in Slovenia. However, this natural phenomenon is ignored in engineering practice as well as in legislation covering hazard assessment and spatial planning. Debris flows are dangerous and can cause large damages and human casualties. Such a case in Slovenia was the November 2000 debris-flow event in Log pod Mangartom. The logical step would be a prescription of a methodology for debris-flow hazard assessment to prevent future events of this kind, but such a preventive step was only taken in the field of floods and flood related erosion. Debris flows are ignored in legislation covering hazard assessment and no changes are expected in the near future. Landslides can be closely related to debris flow initiation and debris flow magnitude and they are key questions when assessing debris flow hazard. The Stože landslide above the village of Log pod Mangartom from November 2000 was analysed with LS-Rapid, a landslide triggering model. With the model we simulated the triggering phase and assessed the landslide volume on the Stože slope. The proposed approach and the gained experiences can be applicable in other torrential areas where potentially unstable areas and landslide-related debris flows present a threat. The proposed approach also presents a first step into the direction of a debris-flow hazard assessment methodology proposal, which should be implemented in national legislation in a similar way as the regulations for flood hazard and flood-related erosion.
Keywords: debris flows; drobirski tokovi; hazard assessment; landslides; LS-Rapid; ocenjevanje nevarnosti; risk management; upravljanje tveganj; zemeljski plazovi